Profile of Pulmonary Tuberculosis Patients with dan without Diabetes at Prof. Dr. H. Aloei Saboe Regional General Hospital Gorontalo City - Siti Nur Rahmatiya Abas; Sugiyarto Surono; Haafizah Dania; Lolita; Endang Darmawan (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Pulmonary tuberculosis (TB) is still a leading cause of death from infectious diseases worldwide, and diabetes mellitus (DM) exacerbates its impact by increasing the risk of infection, worsening clinical manifestations, and lowering treatment success. Objective: To compare the characteristics of pulmonary TB patients with and without DM. Methods: An observational analytic study with a retrospective design was conducted using medical records of pulmonary TB patients at Prof. Dr. H. Aloei Saboe Hospital, Gorontalo, from January to September 2024. Results: TB-DM is most frequently found in the 55–64 years age group, whereas TB without DM is most prevalent in the 45–54 years group. Female patients dominate the TB-DM group, while male patients are more common in the TB without DM group. Conclusion: that age and sex are important determinants in the distribution of TB-DM and TB without DM, emphasizing the need for integrated screening in patients aged ≥45 years and gender-sensitive interventions for TB control.